NK and T Cell Differentiation at the Maternal-Fetal Interface in Sows During Late Gestation - Stas, Melissa R.; Koch, Michaela; Stadler, Maria; Sawyer, Spencer; Sassu, Elena L.; Mair, Kerstin H.; Saalmüller, Armin; Gerner, Wilhelm; Ladinig, Andrea (Frontiers in Immunology, 2020)
The phenotype and function of immune cells that reside at the maternal-fetal interface in humans and mice have been, and still are, extensively studied with the aim to fully comprehend the complex immunology of pregnancy. In pigs, information regarding immune cell phenotypes is limited and mainly focused on early gestation whereas late gestation has not yet been investigated. We designed a unique methodology tailored to the porcine epitheliochorial placenta, which allowed us to address immune phenotypes separately in the maternal endometrium (ME) and fetal placenta (FP) by flow cytometry. In-depth phenotyping of NK cells, non-conventional and conventional T cells within maternal blood (mBld), ME, FP, and fetal spleen (fSpln) revealed major differences between these anatomic sites. In both maternal compartments, all NK cells were perforin+ and had NKp46-defined phenotypes indicative of late-stage differentiation. Likewise, T cells with a highly differentiated phenotype including CD2+CD8α+CD27dim/-perforin+ γδ T cells, CD27-perforin+ CTLs, and T-bet+ CD4+CD8α+CD27- effector memory T (Tem) cells prevailed within these compartments. The presence of highly differentiated T cells was also reflected in the number of cells that had the capacity to produce IFN-γ. In the FP, we found NK cells and T cell populations with a naive phenotype including CD2+CD8α-CD27+perforin- γδ T cells, T-bet-CD4+CD8α-CD27+ T cells, and CD27+perforin- CTLs. However, also non-naive T cell phenotypes including CD2+CD8α+CD27+perforin- γδ T cells, T-bet+CD4+CD8α+CD27- Tem cells, and a substantial proportion of CD27-perforin+ CTLs resided within this anatomic site. Currently, the origin or the cues that steer the differentiation of these putative effector cells are unclear. In the fSpln, NKp46high NK cells and T cells with a naive phenotype prevailed. This study demonstrated that antigen-experienced immune cell phenotypes reside at the maternal-fetal interface, including the fetal placenta. Our methodology and our findings open avenues to study NK and T cell function over the course of gestation. In addition, this study lays a foundation to explore the interplay between immune cells and pathogens affecting swine reproduction.